1972
DOI: 10.4319/lo.1972.17.4.0583
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Decomposition of Sediment and Detritus as a Function of Particle Surface Area and Organic Content

Abstract: Oxygen uptake by microbial populations on mud, sand, and various types of detritus was measured in short-term experiments in aerated water at 20C. Sample size had no effect on oxygen consumption per unit weight, but stirring increased uptake. A 2% Formalin solution completely stopped biological uptake of oxygen by microorganisms on sand and detritus; lake muds showed various degrees of chemical uptake of oxygen.Microorganisms on dead Phrugmites leaves consumed oxygen at an increasing rate during the first few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
1
6

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(143 citation statements)
references
References 19 publications
(5 reference statements)
11
125
1
6
Order By: Relevance
“…In a community, total annual oxygen consumption of sediment surface is a realistic measure of that part of organic material respired in the sediment (Hargrave, 1972;Pamatmat, 1975). Community metabolism is underestimated by measurements of oxygen consumption in a community where anaerobic processes take place.…”
Section: Community Respirationmentioning
confidence: 99%
“…In a community, total annual oxygen consumption of sediment surface is a realistic measure of that part of organic material respired in the sediment (Hargrave, 1972;Pamatmat, 1975). Community metabolism is underestimated by measurements of oxygen consumption in a community where anaerobic processes take place.…”
Section: Community Respirationmentioning
confidence: 99%
“…Several investigators have found an inverse relationship between detritus size and oxygen consumption, a measure of microbial respiration (Hargrave, 1972;Petersen et al, 1989). The larger area-to-volume ratio of smaller particles, and hence the relatively larger available for microbial colonization, is one of the possible explanations of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated a consistent increase in microbial heterotrophic activity as detritus becomes smaller (Hargrave, 1972;Petersen et al, 1989). The nutritive value (e.g., organic matter content) of the sediment and the detritus may be an important predictor of microbial heterotrophic activity, as has been shown for bacteria (Findlay et al, 1986;Cole et al, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…The dried sand in trays may have initially been unattractive to haustoriids or other amphipods (Meadows, 1964;Grant, 1980), but exposure to natural conditions should have restored microbial activity within a few days (e.g. Hargrave, 1972). This factor may have caused colonization to proceed more slowly in the initial stages.…”
Section: Discussionmentioning
confidence: 99%